Bioethics, Vulnerability, and Protection - Macklin, Ruth (Bioethics, 2003)
What makes individuals, groups, or even entire countries vulnerable? And why is vulnerability a concern in bioethics? A simple answer to both questions is that vulnerable individuals and groups are subject to exploitation, and exploitation is morally wrong. This analysis is limited to two areas. First is the context of multinational research, in which vulnerable people can be exploited even if they are not harmed, and harmed even if they are not exploited. The type of multinational research likely to raise the most ethical concerns is that in which the investigators or sponsors are from a powerful industrialised country or a giant pharmaceutical company and the research is conducted in a developing country. Second is the situation of women, who are made vulnerable in cultural settings or in entire countries in which they are oppressed and powerless. In the face of cultural values and practices, or governmental policies, these women suffer serious consequences for their health and even lives. Examples are provided, and it is suggested that in some cases vulnerable individuals can be harmed but not exploited. On the positive side, recent developments reveal a new awareness of exploitation and efforts to enhance the ability of developing countries to protect themselves and their citizens from exploitation at the hands of powerful sponsors of research. In addition, human rights principles are increasingly being used to monitor the actions (or inaction) of governments regarding women's reproductive rights and vulnerability with respect to HIV/AIDS, and to take remedial actions.